Acute abdominal pain as the first symptom of Chlamydia psittaci pneumonia complicated by acute pancreatitis: a case report - Fang, Changquan; Xie, Yanjun; Mai, Hui; Xu, Limin (Frontiers in Medicine, 2023)
Background: Chlamydia psittaci infections primarily cause damage to the lungs but may also affect the cardiovascular system, gastrointestinal tract, liver, kidney, and brain, resulting in a variety of extrapulmonary complications. However, reports regarding C. psittaci infection-associated pancreatitis are rare. In this report, a patient with C. psittaci pneumonia complicated by acute pancreatitis is presented. Case Description: The patient presented with acute upper abdominal pain and developed severe pyrexia and dyspnoea one day later. A chest computed tomography image revealed patchy consolidation in the left lung. The disease progressed rapidly, and the patient exhibited liver and kidney damage and type 1 respiratory failure within a short period of time. Metagenomic next-generation sequencing of alveolar lavage fluid revealed the presence of C. psittaci. The patient was administered doxycycline and moxifloxacin, after which the patient’s abdominal pain and lung infection significantly resolved. Conclusions: This case report demonstrates that extrapulmonary C. psittaci infections due to secondary acute pancreatitis can manifest as abdominal pain, although the exact mechanisms of C. psittaci caused by acute pancreatitis remain unclear. Timely diagnoses and treatments of such infections are necessary to achieve favourable clinical outcomes.